Maize production and processing - Escalante-Ten Hoopen, M.; Maïga, A. (Technical Centre for Agricultural and Rural Cooperation, 2012)
A highly versatile cereal crop, maize is a staple food and can be processed to provide a wide range of products. It is also used in livestock feed and as a raw material in a range of industries. Liberally illustrated with figures, diagrams and tables throughout, this practical guide describes the production of maize and how it can be processed into corn flour. The text clearly outlines the different stages from cultivation up to the production of flour, while a final section offers recipes and further information.